A critical evaluation of strategic market entry theories and practices: the case of Hewlett-Packard. (5th January 2007) - Vrontis, Demetris; Thrassou, Alkis; Wei, Chia-Hung
The choice of correct entry strategy for a particular market is a crucial one for international firms. This research explores entry strategies options and related theories, conducting also a critical evaluation of the advantages and disadvantages of each option and theory. Several frameworks and strategies are identified and developed from different constructs, and the effect of entry strategies on wider international marketing strategies is investigated. This research follows the 'case study' approach based on the Hewlett-Packard market-entry method and a comparison is conducted between two countries: China and the Czech Republic. Furthermore, several key internationalisation issues are identified in terms of the SLEPT (social, legal, economic, political and technological) framework. The results reinforce the belief that before entering a foreign market, a multinational company should construct a detailed marketing plan based on reliable data on every aspect of both the macro and micro-environment of the targeted market.